Kepastian Hukum Pemilik Data Pribadi Dalam Aplikasi Satu Sehat - Tektona, Rahmadi Indra (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2023)
PeduliLindung is a contact tracing application initiated by the Government of Indonesia with the aim of tracking the Covid-19 Virus. However, in its implementation, there have been many criticisms and protests from the public regarding the insecurity of personal data protection in the PeduliLindung application. Moreover, until now Indonesia does not yet have a Personal Data Protection Law. This journal discusses how legal protection is for people who use the PeduliLindung application, as well as a comparison of Indonesian laws with other countries that have previously used contact tracing applications and have regulations regarding personal data. The research method used is literature study by studying journals and related laws.